Pandemic mitigation: Bringing it home - Tom Reichert (Mathematical Biosciences and Engineering)
In the US, national, regional and even institutional plans for ameliorating the effects of pandemic influenza focus on stockpiling antiviral medications, early production and distribution of vaccine, mass and personal social distancing, and a number of personal hygiene activities. Essential personnel are the first scheduled to receive preventive and therapeutic pharmaceuticals, followed by high risk groups, the largest of which are the elderly. Specific recommendations for protection embody a bunker mentality with a time horizon of two weeks, emulating preparation for a natural disaster. The epidemiology of pandemic influenza is scarcely considered.   We summarize here the envelope of mortality attributable to epidemic and pandemic influenza in the last 90 years of the last century as a lead in to a presentation of the multinational case age distribution of the novel H1N1 pandemic of 2009. We discuss the sparing of elderly subpopulations in pandemics and the subsequent abrupt resurgence of mortality in the spared age groups as drift variants emerge. The general decline in the baseline of age-specific excess mortality in economically developed countries is characterized and its importance assessed.   Models of acute and chronic care facilities are discussed and an argument is advanced that society as a whole as well as acute care facilities cannot be protected against incursion and widespread infection in pandemics of severity above low moderate. The key findings of models of chronic care institutions and others that can control public access, such as corporations, are used to describe programs with a realistic chance of providing protection in even severe pandemics. These principles are further mapped onto individual residences. Materials directing institutional and home planning are cited.